Code Mixing Used by English Lecturers in English Language Teaching (ELT) for Non-EFL Students - Tira Nur Fitria (Universitas Pendidikan Indonesia, 2022)
This research is to know the type and reasons for code-mixing used by English lecturers in teaching non-EFL students at ITB AAS Indonesia. This research uses descriptive qualitative. The analysis shows that English lecturers use code-mixing during the English teaching and learning process by inserting Indonesian words, phrases, and clauses. In their utterances, they insert words consisting of parts of speech including pronouns, verbs, adjectives, adverbs, prepositions, and conjunction. They insert phrases including noun phrases, verb phrases, adjective phrases, and adverbial phrases. They also insert clauses including an independent clause. The lecturers use bilingualism such as code-mixing by using two languages both English and Indonesian in the delivery of learning materials and instructional instructions to avoid miscommunication. Therefore, code-mixing is felt to be very necessary to bridge communication in learning between lecturers and students. Practically, the use of code-mixing serves as a way to teach English more easily. Besides, other several reasons for using code-mixing in English language teaching are clarification of ideas and opinions, giving instructions effectively, translation points and notes, socialization and communication, showing linguistics competence, changing/shifting topics, ease of expression, emphasis, and highlighting points, checking understanding, repetitive functions, and create a sense of belonging.